2020
DOI: 10.1128/mra.00771-20
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Metagenome-Assembled Genome of an Uncultured Methyloceanibacter sp. Strain Acquired from an Activated Sludge System Used for Landfill Leachate Treatment

Abstract: Using metagenome sequencing, a nearly complete genome sequence was retrieved for the uncultured Methyloceanibacter sp. strain A49, recovered from an activated sludge system used for landfill leachate treatment at a closed landfill site. The total size and encoded sequences are 3,407,434 bp and 3,280 genes, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…One bacterial MAG matched closely to the marine methylotrophic genus Methyloceanibacter was identified in our study. Other study showed the Methyloceanibacter was also found in the other terrestrial ecosystems (Yasuda et al, 2020), implying that Methyloceanibacter may play key roles in soil CH 4 oxidation of Tibetan alpine grassland. Consistently, the abundance of methanogenic genes (i.e., fmdA) was significantly decreased by warming, whereas methanotrophic genes (i.e., smoA) were significantly increased by warming at this site.…”
Section: Discussionmentioning
confidence: 87%
“…One bacterial MAG matched closely to the marine methylotrophic genus Methyloceanibacter was identified in our study. Other study showed the Methyloceanibacter was also found in the other terrestrial ecosystems (Yasuda et al, 2020), implying that Methyloceanibacter may play key roles in soil CH 4 oxidation of Tibetan alpine grassland. Consistently, the abundance of methanogenic genes (i.e., fmdA) was significantly decreased by warming, whereas methanotrophic genes (i.e., smoA) were significantly increased by warming at this site.…”
Section: Discussionmentioning
confidence: 87%
“…We also found members of the bacterial phyla Atribacterota (g__CG2-30-33-13) and Aerophobota (g__AE-B3A), which are commonly found in methane-rich sediments across various environments such as temperate soils, deep marine sediments, and permafrost 39,40 . We detected several methanotrophic bacteria with high detection, including high-affinity methanotrophs like Methyloceanibacter [41][42][43] and genera from Methylomonadaceae such as g__KS41, which are commonly found in acidic forest soils 44 , and Methyloglobulus, found in lake sediments 45 . Microorganisms involved in carbon and nitrogen cycling processes were also identified.…”
Section: Community Structure Of a 2-million-year-old Microbiomementioning
confidence: 99%
“…The following supporting information can be downloaded at: https:// www.mdpi.com/article/10.3390/microorganisms10061140/s1, Table S1. Chemoautotroph organisms in nif H phylogenetic tree related with diazotrophs from Chile Bay [111][112][113][114][115][116].…”
Section: Supplementary Materialsmentioning
confidence: 99%